2008
DOI: 10.1158/0008-5472.can-07-3225
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 Deficiency Sensitizes Mice to Carcinogen-Induced Tumorigenesis

Abstract: Lkb1 is a central regulator of cell polarity and energy metabolism through its capacity to activate the AMP-activated protein kinase (AMPK)-related family of protein kinases. Germ line-inactivating mutation of Lkb1 leads to Peutz-Jeghers syndrome, which is characterized by benign hamartomas and a susceptibility to malignant epithelial tumors. Mutations in Lkb1 are also found in sporadic carcinomas, most frequently in lung cancers associated with tobacco carcinogen exposure. The basis for Lkb1-dependent tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 44 publications
7
62
0
Order By: Relevance
“…2). These results agree with earlier reports that ectopic LKB1 expression in LKB1-deficient cancer cells blocks the G 1 /S transition (11)(12)(13), and indicate that exogenous activation of LKB1/AMPK signaling is sufficient to induce G 1 arrest, even in cells with endogenous expression of LKB1.…”
Section: Enhanced Expression Of Lkb1 Activates Lkb1/ampk Signaling Insupporting
confidence: 93%
See 2 more Smart Citations
“…2). These results agree with earlier reports that ectopic LKB1 expression in LKB1-deficient cancer cells blocks the G 1 /S transition (11)(12)(13), and indicate that exogenous activation of LKB1/AMPK signaling is sufficient to induce G 1 arrest, even in cells with endogenous expression of LKB1.…”
Section: Enhanced Expression Of Lkb1 Activates Lkb1/ampk Signaling Insupporting
confidence: 93%
“…The finding that in HepG2 cells and HUVECs, the ectopic LKB1 expression leads to an increase in the expression of p53, p21 and p16 is inconsistent with early studies on LKB1-deficient cancer cells, which showed that either p53 or p16 is sufficient for the function of LKB1 in the cell cycle control (11)(12)(13), however, it is in agreement with our previous study reporting, to the best of our knowledge, for the first time that LKB1 targets both p53 and p16 pathways in healthy cells (15). Our results further suggest that in cells with endogenous LKB1 expression, there might be a cross-talk between p53 and p16 pathways, and that these pathways act as important components of LKB1 signaling, which is required for regulating the G 1 /S transition.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…LKB1 is inactivated in patients with Peutz-Jegher's syndrome, a condition that predisposes patients to gastrointestinal hamartomas and malignant tumors in a variety of tissues (Giardiello et al 1987;Hearle et al 2006). Mice with heterozygous disruption of LKB1 develop intestinal neoplasia that mimics human disease in Peutz-Jegher's patients (Bardeesy et al 2002), and complete loss of LKB1 results in resistance to senescence and the development of aggressive cancers (Ji et al 2007;Contreras et al 2008;Gurumurthy et al 2008). The contribution of AMPK to these phenotypes, however, remains unclear as AMPKa1 and a2 are just two of 13 enzymes of the AMPK-related family of kinases activated by LKB1 (Lizcano et al 2004).…”
Section: Metabolic Adaptation By the Ampkmentioning
confidence: 99%
“…Homozygous loss of Lkb1 is embryonically lethal, whereas mice with a heterozygous deletion are tumor prone, showing an increased incidence of spontaneous tumor formation as well as increased susceptibility to toxicity-induced carcinogenesis (Ylikorkala et al, 2001;Jishage et al, 2002;Miyoshi et al, 2002;Gurumurthy et al, 2008). Moreover, Lkb1 þ /À mice develop hamartomatous polyps in the stomach and intestines, but, similar to their human counterparts, these polyps appear to lack or have only low malignant potential (Jishage et al, 2002;Miyoshi et al, 2002).…”
Section: Nf1mentioning
confidence: 99%